DESAIN MODUL PENGUKURAN POTENSI POMPA LISTRIK TENAGA ANGIN (STUDI KASUS PTL-ANGIN KAPASITAS 100 WATT) - Jayadi, Jayadi; Hardiantono, Damis (Faculty of Engineering, Musamus University, Merauke, Indonesia, 2014)
Department of Electrical Engineering, in its further development, is planning to build a Renewable Energy Center especially in the southern region of Papua. In order to support this plan, the data and preliminary research or laboratory are needed as important instruments to develop the renewable energy.This research aims to make a measurement device for measureable variables such as voltage, current, power, and wind speed so that the generation characteristics can be observed. The result of the research is expected to support the laboratory especially for some subjects such as Practicum of Magnitude of Electrical Measurement and Practicum of Renewable Energy and be empirical description for the potential of the wind power electric water pump to support the research / the fulfillment of the need of water for agricultural land in Merauke regency.The method used is the experimental method by making a wind power generator with the capacity of 100 watts, then the output of the generator will be led to a measurement module inside the Electrical Engineering Laboratory. The result shows that the potential of the wind power water pump from July to November (160 days) reached 4.7792 m3 only or about 29.87 liters / day, this result is small according toÂ the design of small capacity turbine utilization. Then, for next development, it would be able to design a turbine with the larger capacity or can be done by using solar cell and integrated installed wind turbines.